2013
DOI: 10.1177/0020764013481427
|View full text |Cite
|
Sign up to set email alerts
|

Training of mental health peer support workers in a non-western high-income city: Preliminary evaluation and experience

Abstract: The programme shows potential benefits for both Warmline service users and trainees. Future studies should compare different training methods and examine the implementation of peer support services in a non-western cultural context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…Tse et al . () found that a good relationship between the MHSU and the trainer is a significant factor affecting the empowerment of the MHSU. In this study, the MHSU serving as a trainer was perceived to create a feeling of closeness and unity among the learners because they had similar experiences of mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Tse et al . () found that a good relationship between the MHSU and the trainer is a significant factor affecting the empowerment of the MHSU. In this study, the MHSU serving as a trainer was perceived to create a feeling of closeness and unity among the learners because they had similar experiences of mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of qualitative and observation research has indicated that organizational factors such as clarity of job description, [ 32 , 33 ] access to appropriate training and support, [ 34 ] shared expectations of the peer worker role, [ 33 , 35 ] and preparation and training for the team that will be working alongside peer workers [ 36 ] are all important facilitators of the introduction of the peer worker role. It has been noted how the distinctiveness of peer support, in comparison to other forms of mental health care, can be lost in a formal environment of statutory mental health services if those organizational conditions are not met.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to countries such as the USA [1,6], Germany, UK, Netherlands, Norway, Slovenia, Sweden [7], Canada, Australia, New Zealand [8] "Experienced Involvement" (EX-IN, peer counselling) programs are predicated on the notion that people with similar experiences can support each other in situations of emotional stress. It was Harry Stack Sullivan who first recruited people recovering from schizophrenia to become his assistants at the clinic for people affected by schizophrenia and nowadays the development of peer supporting in mental health services has spread to Asia, South America and Africa [9]. Although peer support is usually provided independent of conventional mental healthcare, the idea in Poland is that candidates for PWs, after taking the training, would be formally offered a job and become a part of the health system structure.…”
Section: Introductionmentioning
confidence: 99%